Clinical Characteristics of Pediatric Patients With Sellar and Suprasellar Lesions Who Initially Present With Central Diabetes Insipidus: A Retrospective Study of 55 Cases From a Large Pituitary Center in China - Ji, Xin; Wang, Zihao; Wang, Wenze; Gao, Lu; Guo, Xiaopeng; Feng, Chenzhe; Lian, Wei; Deng, Kan; Xing, Bing (Frontiers in Endocrinology, 2020)
Purpose: To increase knowledge for the early differential diagnosis and accurate therapeutic strategies for pediatric patients with sellar or suprasellar region (SSR) lesions who initially present with central diabetes insipidus (CDI). Methods: This is a retrospective review of 55 pediatric patients (≤14 years old) with identified lesions in the SSR who initially presented with CDI at a large pituitary center between 2012 and 2018. The following data were summarized: demographic, clinical, endocrine, and neuroimaging data, intraoperative findings, histopathological findings, treatments, and prognosis. Results: In our group, the etiologies of the SSR lesions included germ cell tumors (GCTs, 74.5%), Langerhans cell histiocytosis (LCH, 18.2%), and craniopharyngioma (CP, 7.3%). Almost all patients (50/55, 90.9%) showed anterior pituitary dysfunction [multiple axes dysfunction (38), and isolated axis dysfunction (14)], while the GH/IGF-I axis was the most affected. Most GCT patients presented with various clinical manifestations besides CDI and had elevated β-HCG, whereas LCH and CP patients mostly presented few non-specific symptoms besides CDI and most had normal level tumor markers. Sellar MRI demonstrated that posterior pituitary bright spot disappearance occurred in all patients, and pituitary stalk thickening was observed in 96.7% of patients. Treatment varied due to the different etiologies of the SSR lesions. After follow-up for 35.4 ± 20.2 months, the proportions of patients who needed AVP (arginine vasopressin) for GCT, LCH, and CP were 86.5, 100, and 75%, respectively, and the proportions of patients who needed HRT were 89.2, 50, and 75%, respectively. Conclusion: For pediatric SSR lesions that first manifest as CDI, we should comprehensively consider clinical characteristics and imaging features to aid in their early differential diagnosis. Tumor markers and surgical histopathology are also great complements for the differential diagnosis. Additionally, various treatment strategies should be adopted according to different causes to improve the child's prognosis and quality of life.